2018
DOI: 10.1096/fj.201801116rr
|View full text |Cite
|
Sign up to set email alerts
|

Brain iron loading impairs DNA methylation and alters GABAergic function in mice

Abstract: Iron deficiency is closely associated with altered GABA metabolism and affective behavior. While mutation in the hemochromatosis (HFE) gene disrupts iron homeostasis and promotes oxidative stress that increases the risk of neurodegeneration, it is largely unknown whether HFE mutation modifies GABAergic homeostasis and emotional behavior. The goal of our study was to investigate the impact of HFE on GABAergic neurochemistry and redox–epigenetic regulation in the brain using H67D HFE‐mutant mice that recapitulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 86 publications
1
22
0
Order By: Relevance
“…6 a, left and right panels). Since iron-overload conditions are associated with epigenetic changes in various human tissues 56 , 57 and epigenetic modification of PAX8 is reported in ovarian cancer 58 , 59 , we next investigated whether FAC-induced increase of PAX8 could be altered with AZA and/or SAHA treatment. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 a, left and right panels). Since iron-overload conditions are associated with epigenetic changes in various human tissues 56 , 57 and epigenetic modification of PAX8 is reported in ovarian cancer 58 , 59 , we next investigated whether FAC-induced increase of PAX8 could be altered with AZA and/or SAHA treatment. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence implicating iron in the regulation of epigenetic control. Specifically, iron deprivation alters DNA methylation and histone deacetylation in preadipocytes 121 whereas brain iron overload reduces DNA methylation 57 . However, the specific underlying mechanism through which iron modulates these events remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that ferroptotic stress directly affects expression of chromatin remodelers and histone PTMs, we wondered whether DNA methylation changes also occur upon RSL3 induction in MM1 cells. Given that prior studies have reported significant global DNA methylation alterations upon intracellular increases in reactive oxygen species (ROS) and iron [33,79,80], we first evaluated changes in global DNA methylation levels in MM1S and MM1R cells treated with 1 µM RSL3 for 72 h. In contrast to prior described experiments (Sections 2.1 and 2.2), cells were treated with subtoxic concentrations of RSL3 (1 µM) to maintain high cell viability upon prolonged (72 h) RSL3 treatment. These prolonged treatment times ensure that de novo DNA methylation changes are also included in the analyses (doubling times of MM1 cells is 72 h).…”
Section: Prolonged Exposure Of Mm1 Cells To Rsl3 Results In Local Dna Methylation Changes and Promotes Expression Of Dna Damage Repair Prmentioning
confidence: 99%
“…Only DNMT1 has been found to inhibit the expression of SOCS1 (which functions as a negative regulator of cytokine signals, including STAT1) through hypermethylation, thereby enhancing M1-like macrophage polarization ( 97 ). Interestingly, different concentrations of exogenous iron (Fe 3+ , 0.0625~0.25 mM) directly decrease the enzyme activity of purified DNMT in vitro ( 98 ). In addition, as mentioned above, FAC supplementation (~0.089 mM Fe 3+ ) suppresses M1-like macrophage polarization by blocking STAT1 pathway in IFN-γ-stimulated RAW264.7 cells ( 35 ); thus, it remains to know whether in some special cases, iron blocks STAT1 pathway through regulating DNA methylation.…”
Section: Mechanisms Whereby Iron Mediates Macrophage Polarizationmentioning
confidence: 99%